Dividual identity in grief theories, palliative and bereavement care. (June 2020) - Davies, Douglas J.
Methods: As in life at large, ideas of 'self' underlie a great deal of theory and practice in palliative care and in bereavement care, they are frequently implicit, being part of shared cultural assumptions, but may assume a degree of theoretical abstraction when fostered by professionals. This article considers the latter, arguing for an interpretation of 'self' influenced by the anthropological notion of dividual or composite personhood and not for that of the autonomous, relatively insular individual typified in much postmodern culture. Results: After depicting both types of personhood, the article explores Western theories of grief typified in the approaches of attachment and loss, continuing bonds with the dead and narrative approaches to identity. Discussion: The dividual approach to personhood then drives a theoretical critique of those grief theories as a means of reflecting upon palliative and bereavement care. Conclusion: This alignment of palliative and bereavement care is seen as an entailment of the dividual approach to personhood, while further consequences are raised for analysing memory, dreams and visitations of the dead, as well as providing a potential perspective upon memory loss and the dissonance experienced by relatives of someone who no longer recognizes them.